A redox modulated fluorescence nanoplatform for the detection of alkaline phosphatase activity with fluorescent polydopamine nanoparticles. Issue 3 (24th December 2020) - Tian, Jing-Xuan; Fang, Yan-Zhao; Yu, Rui; Zhang, Zi-Yan; Zhuo, Yan-Tong; He, Jia-Yu; Wu, Shuang; Xiao, Qiang; Kong, Xiang-Juan
Abstract : Herein, we simply synthesized intrinsic fluorescent polydopamine nanoparticles (PDA NPs) in sodium hydroxide solution (NaOH, pH 11), and constructed a new fluorescence nanoplatform for the detection of alkaline phosphatase (ALP) using PDA NPs as an effective signal reporter. Abstract : Herein, we simply synthesized intrinsic fluorescent polydopamine nanoparticles (PDA NPs) in sodium hydroxide solution (NaOH, pH 11), and constructed a new fluorescence nanoplatform for the detection of alkaline phosphatase (ALP) using PDA NPs as an effective signal reporter. The nanoplatform was constructed by the combination of enzymatic hydrolysis of ALP to the substrate l -ascorbic acid-2-phosphate (AA2P) and the chemical redox reaction between l -ascorbic acid (AA) and mercury ion (Hg 2+ ). The fluorescence of PDA NPs could be effectively quenched by Hg 2+ through the coordination effect between Hg 2+ and the functional groups on the surface of PDA NPs. However, the quenching effect was greatly inhibited by the addition of AA into the solution. Based on this point, the activity of ALP could be monitored by hydrolysis of the substrate AA2P to AA and the fluorescence output of PDA NPs. The nanoplatform exhibited high sensitivity and desirable selectivity for ALP detection. With a wide linear range of 0 to 18 U L −1, a detection limit of 0.4 U L −1 was achieved using the developed nanosensor. The proposed method could not only be used to screen the inhibitor of ALP but also be used to detect ALP activity in human serum samples successfully. Moreover, the strategy can easily be expanded to determining other kinds of enzymes participating in AA-generation reactions.